The Efficiency of BPR/S Industry in Sumatra, Indonesia: Covid-19 Impact, Dual Banking, And Regional Analysis - Mimma; Syahdatul Maulida (SMART Insight, 2022)
Financial institutions are one of the sectors that play a vital role in national and regional economic growth. BPR and BPRS are one of the banking financial industries that play a role in providing financial services to people with a weak economy and MSMEs, so it is necessary to accelerate improvements in BPR and BPRS. This study aims to measure the efficiency and performance of BPRs in Sumatra, see the impact of the pandemic on BPR and BPRS operations and conduct regional analysis on BPRs and BPRS in Sumatra. Using a sample of 30 BPRs and 30 BPRS in Sumatra, this study conducted observations during the 2016-2021 period. This study uses the Data Envelopment Analysis (DEA) analysis method with secondary data sourced from the financial statements of each BPR and BPRS. The input variables in this study are fixed assets, operating expenses and third-party funds. Meanwhile, the output variables of this research are the financing provided and operating income. The results of the study revealed that the average BPR and BPRS in Sumatra during the 2016 to 2021 period fluctuated. Then, in the CRS and VRS analysis, Lampung and North Sumatra regions have the highest efficiency compared to other regions. Meanwhile, during the Covid-19 pandemic, both BPRs and BPRS in Sumatra experienced a significant decrease in efficiency. This study also analyzes potential improvements to improve programs that cause inefficiencies in the input and output variables. In general, the causes of inefficiency of the two types of banks are operating income and the amount of financing provided. This study also provides recommendations to BPR-BPRS practitioners, regulators and academics as a basis for decision making in achieving optimal efficiency for future.